The thin blue line : how humanitarianism went to war - Foley, Conor (London ; New York : Verso, 2010)
Foley explores how the doctrine of humanitarian intervention has bee n used to allow states to invade other nations in the name of human rig hts. Drawing on his own experience of working in over a dozen conflict and post-conflict zones, he shows how the growing influence of internat ional law has been used to override the sovereignty of the poorest coun tries in the world.
Human rights and humanitarianism -- Humanitarian interventions -- Ko sovo -- Afghanistan -- Sri Lanka and Indonesia -- A responsibility to p rotect -- Justice and peace -- Humanitarian accountability -- Conclusio n. The new imperialists?
Includes bibliographical references (p. [241]-260) and index.
Keywords: Humanitarian intervention; Humanitarian assistance -- Corrupt practices